Retentive force of conical crowns combining zirconia and fiber-reinforced composite - Tasaka, Akinori; Rues, Stefan; Schwindling, Franz Sebastian; Rammelsberg, Peter; Yamashita, Shuichiro (Journal of dentistry, 2022)
Purpose: This study investigated the retentive force of conical crowns combining zirconia primary and fiber-reinforced composite (FRC) secondary crowns and their changes due to aging. Methods: Zirconia primary crowns were produced with a convergence angle of 3 degrees. Thirty-two secondary crowns were milled from FRC and divided into two groups (n = 16/group) based on the polishing method of the secondary crown inner surfaces: diamond paste (Group 1) and silicone points (Group 2). After fitting the secondary crowns with different fitting forces (F), loosening forces (L) were determined. Tests were repeated after an occlusal stop (OS) was added to the secondary crown and artificial aging (10,000 insertion/removal cycles). Data were compared using the Wilcoxon and Mann-Whitney U tests. Results: Crowns without an OS showed L/F ratios of 0.4586 (Group 1) and 0.4104 (Group 2). With an OS, maximum retention was not significantly affected by the polishing method and could be limited to L-max = 19.31 +/- 7.77 N (Group 1) and L-max = 16.12 +/- 5.92 N (Group 2). Conclusions: These findings suggest that the combination of conical zirconia primary and FRC secondary crowns can obtain acceptable retentive forces that are not affected by aging if the inner surfaces are polished with diamond paste. OS generation could limit maximum retention, but should be adjusted if the target value of 10 N is not to be exceeded. With a change of the convergence angle to 4 degrees, L/F values for crowns without an OS would be close to 1/3, which is considered ideal for conical crowns. Clinical significance: The combination of zirconia primary crowns and FRC secondary crowns was found feasible to ensure the required retention for clinical use over a long time span. Furthermore, it offers an alternative to metal-based restorations while ensuring high levels of biocompatibility and esthetics.
Gesehen am 22.12.2022